Pemenuhan Hak Pendidikan Anak Korban dari Eksploitasi Orang Tua - Yanti Mulyawati; Abdul Rohman (Jurnal Riset Ilmu Hukum, 2024)
Abstract The case of exploitation of school-age children is contrary to the State's objectives, which are stated in the fourth paragraph of the Preamble to the 1945 Constitution of the Republic of Indonesia, namely to make the nation's life intelligent. Apart from that, regulations regarding the importance of fulfilling the rights of children at school age are regulated in Law number 35 of 2014 concerning Child Protection (Child Protection Law), which states that every child has the right to receive education and teaching in the context of their personal development and level of intelligence in accordance with interest and talent. The majority of the population in Indonesia is from a Muslim background, whose teachings place great importance on fulfilling children's rights, apparently this is not a guarantee as a solution to the success of the country's goals in Indonesia.  In connection with this, the author is very interested in researching it with the thesis research title "Fulfillment of Children's Educational Rights from Victims of Parental Exploitation in View of Child Protection Laws and Islamic Law". The problem formulation of this research includes: (1) How are the educational rights of children victims of parental exploitation fulfilled based on the Child Protection Law and Islamic Law? (2) What is the solution to the educational rights of children who are victims of parental exploitation based on the Child Protection Law and Islamic Law? The author conducted research using normative juridical methods, namely qualitatively collecting research material obtained through literature study. Thus, the data collected is analyzed against statutory regulations and other legal sources such as Islamic law, as well as other data that supports the answer to the problem being researched so that it is close to accuracy.The results of this research include: (1) Fulfillment of the educational rights of children who are victims of parental exploitation, both based on the Child Protection Law and Islamic Law, has not been optimally implemented in Indonesia. This can be seen from the data produced in the author's research, that there is still quite a large amount of exploitation of children at school age, reaching 3.3 million children out of school in several big cities in Indonesia, even though Islamic law is supposed to be a guide to life for Muslims as residents. The largest in Indonesia, in its teachings, it is mandatory for every parent to prepare a strong generation in the future. (2) The solutions that the author tries to recommend based on the research that has been carried out are: (1) Law enforcement as regulated in the Child Protection Law with legal certainty by the government in order to realize the national goal, namely to make the nation's life intelligent with full responsibility; (2) Maximizing the role of religious institutions and community figures so that the fulfillment of the educational rights of children who are victims of child exploitation can be minimized, as well as providing outreach on the importance of children's education both according to positive Indonesian law and Islamic law Abstrak Eksploitasi anak usia sekolah bertentangan dengan tujuan konstitusional Indonesia, sebagaimana tercantum dalam Pembukaan UUD 1945, yaitu mencerdaskan kehidupan bangsa. UU No. 35 Tahun 2014 tentang Perlindungan Anak menegaskan hak anak atas pendidikan untuk pengembangan pribadi dan intelektual. Meski ajaran Islam, yang dianut mayoritas penduduk Indonesia, juga menekankan pentingnya hak anak, eksploitasi anak tetap menjadi masalah. Penelitian ini, berjudul “Pemenuhan Hak Pendidikan Anak Korban Eksploitasi Orang Tua Ditinjau dari Undang-Undang Perlindungan Anak dan Hukum Islam,” membahas dua pertanyaan utama: (1) Bagaimana pemenuhan hak pendidikan anak korban eksploitasi menurut UU Perlindungan Anak dan Hukum Islam? (2) Apa solusi efektif untuk memenuhi hak tersebut? Melalui pendekatan yuridis normatif, penelitian ini menemukan bahwa pemenuhan hak pendidikan anak korban eksploitasi belum optimal. Data menunjukkan 3,3 juta anak tidak bersekolah, mencerminkan eksploitasi yang terus berlangsung. Solusi yang diusulkan mencakup penegakan hukum yang lebih tegas berdasarkan UU Perlindungan Anak, keterlibatan aktif lembaga agama dan tokoh masyarakat, serta edukasi publik tentang pentingnya hak-hak anak dalam perspektif hukum dan Islam untuk memastikan akses pendidikan.